INCREASE IN HEPATIC QUINOLINIC ACID CONCENTRATIONS IN ALCOHOL WITHDRAWN RATS - Bano, Samina; Ara, Iffat; Naseem, Warda (Journal of Ayub Medical College Abbottabad, 2019)
Background: Behavioral associated disturbance involves excitotoxic quinolinate in alcohol withdrawal syndrome in man due to increase availability of tryptophan. In present study we investigated alcoholism related clinical features in relation to tryptophan and 5-HT levels in rat's model. Methods: Locally bred male Wistar rats, weighing 200-250 g were housed separately into 6 animals/ group with 12 h light: dark cycle at room temp 22±3 °C. They were given diet ad libitum, for three days then alcohol 8% (v/v) was added into the liquid diet. Matched control rats of each group were given maltose-dextrin as a substitute of alcohol. Alcohol withdrawal syndrome was assessed after 7 hours by replacing the alcohol-containing liquid diet with tap water. Results: Alcohol withdrawal group showed significant increase (p<0.001) in holo, apo, and total tryptophan 2, 3 dioxygenase enzyme activities, no significant change in brain tryptophan and 5HIAA however significant decrease (p<0.001) in brain 5HT was observed when compared with chow controls. Both alcohols administered and withdrawal groups showed significant rise in serum corticosterone by p<0.05 and p<0.001 respectively. Liver quinolinic acid concentrations were increased significantly (p<0.01) with robust increase in alcohol withdrawn rats. Conclusion: We conclude that the excitotoxin tryptophan metabolite quinolinic acid of peripheral origin plays significant role in the behavioral manifestation of the alcohol withdrawal syndrome. Tryptophan metabolites should be targeted to develop new strategies in the progress of pharmacological interventions related to alcoholism. Keywords: Ethanol; Quinolinic acid; Tryptophan metabolism; Alcohol withdrawal; tryptophan 2,3 dioxygenase; 5-hydroxytryptamine; rats